PENGARUH AUDIOVISUAL TERHADAP PENINGKATAN PENGETAHUAN KEPALA KELUARGA DALAM MELAKSANAKAN CUCI TANGAN PAKAI SABUN (AUDIOVISUAL EFFECT ON KNOWLEDGE IMPROVEMENT OF FAMILY HEADS IN IMPLEMENTING HAND WASHING WITH SOAP) - yansen parlaungan tambunan; Yehud Maryen; Oktovina Mobalen; Panel Situmorang (Poltekkes Kemenkes Medan, 2021)
Introduction: Hand washing with soap with running water is the most cost-effective way to protect us from infectious diseases. Objective: To analyze the effect of the audiovisual method intervention on improvement the knowledge of family heads implementing hand washing with soap in the city of Sorong. Methods: This type of research is a quantitative study with a quasi experimental design research type with the design used is time series design. There are 30 of family heads in RT 03/RW 05 of Klasaman sub-district, Sorong city as respondent in this research. Results: The study showed that there was an effect of using the audiovisual method hand washing with soap (CTPS) on knowledge improvement of family heads in the city of Sorong with the sig. value (2 tailed) was 0.000 <0.05, which means there was a difference in the knowledge of the pre-test and post-test of family heads treatment group. Conclusion: Can be used as learning tools in providing information and education to the community, especially family heads so as to improvement knowledge to carry out hand washing with soap with running water.